2016
DOI: 10.1002/ece3.2352
|View full text |Cite
|
Sign up to set email alerts
|

Genetic connectivity across marginal habitats: the elephants of the Namib Desert

Abstract: Locally isolated populations in marginal habitats may be genetically distinctive and of heightened conservation concern. Elephants inhabiting the Namib Desert have been reported to show distinctive behavioral and phenotypic adaptations in that severely arid environment. The genetic distinctiveness of Namibian desert elephants relative to other African savanna elephant (Loxodonta africana) populations has not been established. To investigate the genetic structure of elephants in Namibia, we determined the mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
(138 reference statements)
2
10
0
Order By: Relevance
“…One possible reason for this pattern is that highly encephalized birds have lower risk of extirpation during the early stages of colonization (i.e., when abundances are low 43 ), because of their enhanced ability to withstand environmental change. Similar links between cognition and range expansion have been made in studies documenting the success of highly encephalized species in colonizing novel habitats 16,17,41 and are the basis of our current understanding of the process of human expansion out of Africa 8,44 . Overall, our results suggest that even though environmental variability can be a viable agent of selection in the evolution of cognition (as also concluded by 14,45 ), this particular mechanism is unlikely to have driven many of the most striking cases of encephalization among birds.…”
Section: Did Larger Brains Evolve In More Variable Environments?supporting
confidence: 53%
See 1 more Smart Citation
“…One possible reason for this pattern is that highly encephalized birds have lower risk of extirpation during the early stages of colonization (i.e., when abundances are low 43 ), because of their enhanced ability to withstand environmental change. Similar links between cognition and range expansion have been made in studies documenting the success of highly encephalized species in colonizing novel habitats 16,17,41 and are the basis of our current understanding of the process of human expansion out of Africa 8,44 . Overall, our results suggest that even though environmental variability can be a viable agent of selection in the evolution of cognition (as also concluded by 14,45 ), this particular mechanism is unlikely to have driven many of the most striking cases of encephalization among birds.…”
Section: Did Larger Brains Evolve In More Variable Environments?supporting
confidence: 53%
“…However, in order to evaluate the extent to which this mechanism provides a general explanation for the evolution of cognition in birds, it is critical to explore the direction of causality in the correlation between an enhanced potential for cognition and the occupancy of variable environments. A clear understanding of the sequence of evolutionary events is particularly necessary in this context because the adaptive benefits invoked by the cognitive buffer hypothesis may just as well promote the evolution of cognition in variable habitats, or facilitate instead the secondary colonization of variable habitats by already highly encephalized species 41 . We evaluated the support for these two non-mutually exclusive evolutionary scenarios by using reversible-jump MCMC to estimate models of correlated trait evolution 42 fitted to an exhaustive global sample of non-migratory birds for which brain size is known (N = 1,288 species; Supplemental Data 2).…”
Section: Did Larger Brains Evolve In More Variable Environments?mentioning
confidence: 99%
“…Other studies have demonstrated that elephant can survive extreme climate as indicated in the studies in Namibia [38] and increasing elephants in Botswana [39], where the condition are much severe than our study area. In Kajiado the other drivers like settlements, agriculture, land subdivision and developments may impact the elephants negatively.…”
Section: Discussionmentioning
confidence: 42%
“…To test for structure on an evolutionary timescale, we analyzed genotypes in STRUCTURE 2.3.4 (Pritchard et al, 2000), denoting a model-based clustering algorithm to multi-locus genotype data (Ishida et al, 2016). We programmed length of the burn-in period to 10,000 and the number of Markov Chain Monte Carlo (MCMC) reps after the burn-in to at least 100,000 steps.…”
Section: Genetic Analysismentioning
confidence: 99%
“…A species' ability to cope with the changing selective forces resulting from anthropogenic disturbance may be partially determined by the amount of genetic variability in populations as well as the way that variation is structured within and between populations (Archie et al, 2011;Ishida et al, 2016). Evidence for recent emergence of genetic structure within the three studied elephant populations suggests that habitat loss and fragmentation in the areas between Ruaha and Katavi are starting to alter population connectivity.…”
Section: Management Implicationsmentioning
confidence: 99%